Kenya : Request for Extension of the Stand-By Arrangement -- Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2018)
This paper discusses Kenya's Request for Extension of the Stand-by Arrangement (SBA). The extension is needed to provide additional time for the authorities to bring the program back on track and reach new understandings with IMF staff on policies and measures that would enable the completion of the pending reviews under the SBA for Kenya. The authorities have committed to strong corrective actions through adopting policies that will enable them to achieve program objectives and reduce near- and medium-term vulnerabilities. The IMF staff supports the authorities' request for an extension of the SBA for Kenya.